Lymphoepithelioma-Like Carcinoma of the Bladder: A Case Report and Review of the Literature. (22nd April 2013) - Mori, Kenichi; Ando, Tadasuke; Nomura, Takeo; Sato, Fuminori; Mimata, Hiromitsu
Abstract : Lymphoepithelioma-like carcinoma (LELC) in the bladder is uncommon with a reported incidence of 0.4%–1.3% of all bladder carcinomas. In Japan, some occurrences of LELC have been reported in the renal pelvis and ureter but only two in the bladder. A bladder tumor was identified in a 70-year-old man suffering from macroscopic hematuria for 2 months. Sections of the transurethral tumor resection showed invasive high-grade urothelial carcinoma. The patient was diagnosed with local invasive bladder tumor, and cystectomy with ileal conduit formation was performed. The final pathological evaluation was predominant LELC with urothelial carcinoma. We present a new case of LELC in the bladder and performed a review of all published cases of LELC in the urinary tract to obtain its characteristics and prognostic guide.